Role of Certain Diet and Body Mass Index on Severity of Acne - Hero Hammad Azeez, Intiha Muhamad Reda, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Acne vulgaris (AV) is one of the most prevalent chronic dermatological conditions among adolescents. Recent data indicated that a certain diet may influence the development and appearance of acne. Materials and methods: This was a cross sectional study conducted in the outpatient department of Erbil dermatology teaching center from May 2022 to December 2022. All the newly diagnosed patients with acne were included in the study. Height and weight of the patients was recorded and BMI was calculated. BMI was categorized as underweight, normal weight, overweight and obese. Type of lesions was noted and severity of acne was graded from 1 to 4. Result: In this study, 27 patients (27%) were male and 73 patients (73%) were female. The highest rate of AV was seen in age group 16-20years and the lowest rate was observed in age group ≥21 years. Moderate to severe acne was strongly associated with a family history of acne in first-degree relatives (P= 0.0141). There was a significant association between Acne treatment received (<0.0007) and smoking habit (<0.0001) with severity of acne. The risk increased with increased red meat consumption (P= 0.0486). Majority of patients (62%) had normal BMI. Most of the patients had Grade 1 acne (20%). There was no significant association between the BMI and severity of acne (p= 0.3094) Conclusion: BMI are not risk factors for severity of AV, but a family history of acne is. Severity of AV is related to receiving acne treatment, cosmetic use, smoking habit and red meat Keywords: Acne vulgaris, family history, age, diet, body mass index